Implications of Research on the Readiness of Occupational Health Post Establishment for Online Ojek Drivers - Rohmah, Nur; Tri Agustini, Rina; Lusiana Setyowati, Dina (Faculty of Public Health Mulawarman University, Indonesia, 2025)
Background : The advent of online taxi bike drivers has revolutionized the lives of Indonesians by providing a convenient and effective means of transportation. Despite the issue, it was shown that in 2017, 79% (58,715 incidents) of online taxi bike drivers were engaged in traffic accidents. One of the reasons for the large number of accidents is the health of the drivers. Objective : The purpose of this study is to identify the needs of informal health services for online motorcycle taxi drivers. Research Methods/ Implementation Methods : the Community Meeting (In Indonesia: Musyawarah Masyarakat Desa/MMD). This meeting was attended by 16 people, consisting of 3 researchers, 3 people from the Samarinda City Health Office, 1 representative from Juanda Health Center, 2 people from Samarinda City Health Center, 1 person from Remaja Health Center, 1 person from Wonorejo Health Center, and 5 people from the regional office. Results : Based on the Community Meeting results, it is known that each regional office and community health center needs further coordination related to the initiation of Occupational Health Post. The regional office can prepare a minimum of 4 Occupational Health Post cadres and this study targets 10 partners from each regional office. Despite the wide availability of formal health services, informal health services are an important component needed by the community including online ojek drivers. The results of the community deliberation meeting consisted of four themes, namely: Schedule for the implementation of the Occupational Health Post , Legality of the establishment of Occupational Health Post , Coordination with local villages, Flow of implementation of the Occupational Health Post Conclusion/Lesson Learned : Based on the results of the deliberation, preparation is needed for the establishment of the Occupational Health Post. There are two activities, namely training ojek driver members to be trained as Occupational Health Post health cadres and advocacy in the establishment of Occupational Health Post